If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + -4x)(5 + -2x) = 6 Multiply (6 + -4x) * (5 + -2x) (6(5 + -2x) + -4x * (5 + -2x)) = 6 ((5 * 6 + -2x * 6) + -4x * (5 + -2x)) = 6 ((30 + -12x) + -4x * (5 + -2x)) = 6 (30 + -12x + (5 * -4x + -2x * -4x)) = 6 (30 + -12x + (-20x + 8x2)) = 6 Combine like terms: -12x + -20x = -32x (30 + -32x + 8x2) = 6 Solving 30 + -32x + 8x2 = 6 Solving for variable 'x'. Reorder the terms: 30 + -6 + -32x + 8x2 = 6 + -6 Combine like terms: 30 + -6 = 24 24 + -32x + 8x2 = 6 + -6 Combine like terms: 6 + -6 = 0 24 + -32x + 8x2 = 0 Factor out the Greatest Common Factor (GCF), '8'. 8(3 + -4x + x2) = 0 Factor a trinomial. 8((1 + -1x)(3 + -1x)) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {1, 3}
| (36x^2)+(36y^2)-144=0 | | -6n=-31.26 | | y=35000+.45x | | 20=9+x | | 3x-12/4=6 | | -7(3+t)=4(2t+6) | | 2x+5+3x+15=90 | | c/8+16=7 | | 15-(-10x)5x-(-9)= | | 8x^5-12x^2+2x-3=0 | | 1+8y-14y= | | 1/(2a^2-4a-6)=(a+2)/(2a^2-4a-6)-1 | | 550.00x+175000.00=220650 | | 0.10x+0.05(4-x)=0.10(-5) | | -x^2+5x-104=0 | | 1680x+35000.00=300440 | | n+10=24+8n | | -5d(3d^2+2)=0 | | 1680.00x+35000.00=220650 | | Y^2-6=5y | | -96=5x+6(-2x-9) | | 1680.00x+35000.00= | | 2x+2y+70=180 | | 2t^2+8x-64=0 | | 2k-20=3k | | 2=sqrt(-3w+76) | | 550.00x+175000.00=1680.00x+35000.00 | | -6+3x=-6x-33 | | (17g-10)=(14g+20) | | 10y^3+29y^2+40y-100=0 | | -7x+4=-14 | | 3(h-2)=36 |